Recent Advances in Autism Spectrum Disorders Volume I - Fitzgerald, Michael (IntechOpen, 2013)
The pace of research on Autism Spectrum Disorders (ASD) can only be described as extraordinary as this volume shows. It is extremely difficult for any single professional to keep abreast of all the developments in this area. This volume gathers together leading researchers and expert clinicians from many different parts of the world to produce this "up-to-the-minute" volume. It gives an in depth view of many areas of research which may be unfamiliar to the clinician and indeed researcher focused on their own area of interest. The volume gives an in depth overview of the field of Autism Spectrum Disorders.